GCG, CORPORATE CHARACTERISTICS, AND FINANCIAL DISTRESS AS A DETERMINANT OF EXTENSIVE VOLUNTARY DISCLOSURES - Indri Kartika; Icca Pramadila; Sri Sulistyowati (Riset Akuntansi Keuangan, 2021)
The existence of a conflict of interest between the principal and theagent causes information asymmetry. This information asymmetry canbe minimized by voluntary disclosure in the annual report. GCGfactors, company characteristics, and financial distress are predicted toinfluence the extensive voluntary disclosure. This study aims to examinethe effect of ownership dispersion, financial distress, the board size,CEO duality and age of listings on the extensive voluntary disclosure.Data population are basic and chemical industry companies listed onIDX for the 2015-2018. A purposive sampling was used as method andobtained 160 samples. This study used secondary data from annualreports. Data were analyzed by using the Multiple Linear RegressionAnalysis method. This study found that Ownership Dispersion and Sizeof the Board of Commissioners have a significant positive effect onExtensive Voluntary Disclosure. Whereas Financial Distress, CEODuality, and Age of Listing have no significant effect on ExtensiveVoluntary Disclosure.